Reducing the Use of Complex Words and Reducing Sentence Length to <15 Words Improves Readability of Patient Education Materials Regarding Sports Medicine Knee Injuries - Stefan J. Hanish, B.S; Nathan Cherian, M.D; John Baumann, B.S; Samuel D. Gieg, M.D., M.P.H; Steven DeFroda, M.D., M.Eng (Elsevier, 2023)
Purpose: To develop a standardized method to improve readability of orthopaedic patient education materials (PEMs) without diluting their critical content by reducing the use of complex words (≥3 syllables) and shortening sentence length to ≤15 words. Methods: OrthoInfo, a patient education website developed by the Academy of American Orthopedic Surgeons, was queried for PEMs relevant to the care of athletic injuries of the knee. Inclusion criteria were PEMs that were unique, pertained to topics of knee pathology in sports medicine, and written in a prose format. Exclusion criteria were information presented in video or slideshow format, or topics not pertaining to knee pathology in sports medicine. Readability of PEMs was evaluated using 7 unique readability formulas before and after applying a standardized method to improve readability while preserving critical content (reducing the use of ≥3 syllable words and ensuring sentence length is ≤15 words). Paired samples t-tests were conducted to assess the relationship between reading levels of the original PEMs and reading level of edited PEMs. Results: Reading levels differed significantly between the 22 original PEMs and edited PEMs across all 7 readability formulas (P < .01). Mean Flesch Kincaid Grade Level of original PEMs (9.8 ± 1.4) was significantly increased compared to that of edited PEMs (6.4 ± 1.1) (P = 1.9 × 10-13). 4.0% of original PEMs met National Institutes of Health recommendations of a sixth-grade reading level compared with 48.0% of modified PEMs. Conclusions: A standardized method that reduces the use of ≥3 syllable words and ensures sentence length is ≤15 words significantly reduces the reading-grade level of PEMs for sports-related knee injuries. Orthopaedic organizations and institutions should apply this simple standardized method when creating PEMs to enhance health literacy. Clinical Relevance: The readability of PEMs is important when communicating technical material to patients. While many studies have suggested strategies to improve the readability of PEMs, literature describing the benefit of these proposed changes is scarce. The information from this study details a simple standardized method to use when creating PEMs that may enhance health literacy and improve patient outcomes.